Laparo-endoscopic Transanal Total Mesorectal Excision (TATME): evidence of a novel technique. Issue 5 (2nd September 2016) - Araujo, Sergio Eduardo Alonso; Perez, Rodrigo Oliva; Seid, Victor Edmond; Bertoncini, Alexandre Bruno; Klajner, Sidney
Abstract: Current available evidence regarding transanal total mesorectal excision (TATME) was analyzed including perioperative and immediate oncologic outcomes. A literature search of PubMed, Embase and Cochrane was performed. Thirty-two studies were identified, reporting on 721 patients who underwent TATME. TATME represents a feasible and reproducible technique. Nevertheless, the results of the present review are limited by the design of the included studies, which are mostly case reports and case series. Little is known about long-term oncologic outcomes, intestinal, sexual, urinary function and quality of life after TATME. Multicenter large sample randomized controlled trials are required for further investigation of these issues.